Do Not Forget the Diseases Apart from Covid-19! Its High Morbidity Illness: Evidence from Indonesia and The Philippines - Amril Mukmin; Al Fauzi Rahmat (Indonesian Journal of Global Health Research, 2025)
Along with the Coronavirus Diseases (or called “COVID-19”) pandemic, most of the world’s population is affected by global endemic diseases that have been around for a long period of time, so it can affect the additional burden on a country's healthcare system such Indonesia and the Philippines as case study. Therefore, this article aims to evaluate the rate of endemic disease and COVID-19, as well as to review the healthcare system and resources in Indonesia and the Philippines. We conducted a specific analysis based on official health documents by the government and previous literature; also, news portals were conducted. Our findings note that is a shift in the contribution of the healthcare system in Indonesia and the Philippines due to relatively high surveillance of the spread of COVID-19, as a consequence in the centralization of health budgets and resources for the prevention of COVID-19 disease as opposed to endemic diseases. Indeed, some endemic disease morbidity is reported to be higher than the COVID-19 pandemic. In the end, Indonesia and the Philippines are faced with the unexpected, where it has been proven that endemic diseases still exist during the COVID-19 pandemic and future healthcare spending